2009
DOI: 10.1080/10790268.2009.11760761
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Therapies for Spinal Cord Injury

Abstract: Spinal cord injury (SCI) results in loss of nervous tissue and consequently loss of motor and sensory function. There is no treatment available that restores the injury-induced loss of function to a degree that an independent life can be guaranteed. Transplantation of stem cells or progenitors may support spinal cord repair. Stem cells are characterized by self-renewal and their ability to become any cell in an organism. Promising results have been obtained in experimental models of SCI. Stem cells can be dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 138 publications
(137 reference statements)
0
58
0
1
Order By: Relevance
“…Neural stem cells (NSCs) can differentiate into neurons, oligodendrocytes (OLs), and astrocytes, and are a promising candidate for cell transplantation to treat spinal cord injury (SCI) [1]. Recently, NSC-based therapy of SCI has been attempted in numerous animal experiments and produced encouraging results [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural stem cells (NSCs) can differentiate into neurons, oligodendrocytes (OLs), and astrocytes, and are a promising candidate for cell transplantation to treat spinal cord injury (SCI) [1]. Recently, NSC-based therapy of SCI has been attempted in numerous animal experiments and produced encouraging results [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NSC-based therapy of SCI has been attempted in numerous animal experiments and produced encouraging results [1][2][3][4]. However, the studies also found that after transplantation into the injured spinal cord, most NSCs differentiate into astrocytes, but not OLs and neurons [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent pathological studies have suggested that the difficulties of functional recovery after SCI mainly included the survival of cells, regeneration of axons, the precise location of regenerative axons, and accurate reformation and functional synaptic connections (Nandoe Tewarie et al, 2009). Because NSCs have the potential to differentiate into neurons (Lee et al, 2012), oligodendrocytes, and axons (Decimo et al, 2011;Yasuda et al, 2011) and also have the ability to fill the spinal cord cavity and blend with host spinal cord tissues (Boido et al, 2011;Li et al, 2011), they may be useful for repairing SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based therapies using adult bone marrow-derived progenitor/stem cell technologies might also prove highly successful for the treatment of fibrosis [136][137][138]. Since fibrocytes and EMT-derived myofibroblasts produce a variety of factors that are involved in the fibrotic process recruitment and/or activation could provide a unique therapeutic approach to treat a variety of fibrotic diseases.…”
Section: An Overview On the Phenomena At Cellular Scalementioning
confidence: 99%